2021
DOI: 10.3389/fped.2021.682839
|View full text |Cite
|
Sign up to set email alerts
|

The Albumin-to-Fibrinogen Ratio Independently Predicts Acute Kidney Injury in Infants With Ventricular Septal Defect Undergoing Cardiac Surgery With Cardiopulmonary Bypass

Abstract: Background: Acute kidney injury (AKI) is a common and serious complication faced by children following ventricular septal defect (VSD) surgery with cardiopulmonary bypass (CPB). The objective of this study was to explore potential predictors inherent to AKI.Methods: VSD infants who were scheduled for elective cardiac surgery with CPB from 2017 to 2020 were enrolled in this study. Based on the Pediatric Risk, Injury, Failure, Loss, End-Stage Renal Disease (pRIFLE) criteria, patients were divided into AKI and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, study by Godinez-Vidal et al reported that albumin can be considered a predictor of severity, although not a predictor of mortality [ 34 ]. Serum fibrinogen expression is notably increased in patients with a high inflammatory status and can promote the activation of coagulation and aggregation of PLT [ 16 , 35 ]. Previous studies have shown that dysregulation of fibrinogen expression leads to a poor prognosis of disseminated intravascular coagulation in patients with sepsis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, study by Godinez-Vidal et al reported that albumin can be considered a predictor of severity, although not a predictor of mortality [ 34 ]. Serum fibrinogen expression is notably increased in patients with a high inflammatory status and can promote the activation of coagulation and aggregation of PLT [ 16 , 35 ]. Previous studies have shown that dysregulation of fibrinogen expression leads to a poor prognosis of disseminated intravascular coagulation in patients with sepsis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…AFR, the ratio of albumin to fibrinogen, can be used as a timely indicator of the nutritional status, inflammatory status, and coagulation function of patients [36][37][38] and is also an effective marker to predict the prognosis of various diseases, including lung cancer, rheumatoid arthritis, and acute kidney injury [16,36,39]. The prognosis of sepsis is closely associated with nutritional status, inflammatory status, and coagulation function of patients [4].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The innovative inflammation-based risk metric, known as the fibrinogen-to-albumin ratio (FAR), has demonstrated its value in predicting adverse outcomes in cancer ( 9 , 10 ) and cardiovascular disease ( 11 13 ). Recent studies has indicated that the levels of preprocedural FAR exhibit a correlation with the incidence of AKI in individuals undergoing emergency percutaneous coronary intervention ( 14 ) and elective percutaneous coronary intervention ( 15 ) and in children following ventricular septal defect surgery ( 16 ). Nevertheless, the association linking the frequency of acute kidney injury (AKI) in individuals who have undergone cardiac surgery and the previously unexplored variable, known as FAR, remains uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…Especially when combined with albumin, the albuminfibrinogen-ratio (AFR), was demonstrated to improve the prognostic accuracy as compared to albumin or fibrinogen alone within various clinical conditions [14][15][16]. Albumin is produced in the liver and is responsible for the maintenance of colloid osmotic pressure.…”
Section: Introductionmentioning
confidence: 99%